Duka mendalam: Bagaimana keluarga korban tragedi kanjuruhan manghadapi kehilangan - Mufidah, Do’aul Isma (Maliki Interdisciplinary Journal, 2024)
The purpose of this article is to examine the psychological and social emotional impact experienced by the families of the victims of the Kanjuurhan tragedi and the strategies used to cope with the loss. The Kanjuruhan tragedi was a disaster in the world of soccer that not only empathized the domestic community, but also the international community. The tragedi that caused 135 deaths and hundreds of injuries must have been a very heavy blow to the families of the victims. They experienced serious emotional and psychological impacts. In addition to their mental, emotional, and mental wounds, they also experienced changes in the dynamics of their families. To overcome these things, several efforts can be made such as emotional support, therapeutic counseling services, spiritual and religious approaches and financial assistance.